EFFECT OF HIGH DOSE FIMASARTAN ON CHANGES OF DAYTIME AND NIGHTTIME BLOOD PRESSURE COMPARED TO HIGH DOSE VALSARTAN. (June 2018) - Chung, W.-B.; Ihm, S.; Jang, S.; Hur, S.; Lee, J.; Jeon, D.; Yoo, K.; Chang, K.; Seung, K.
Abstract : Objective: : Head-to-head comparison of blood pressure lowering effect of fimasartan (FMS) to other angiotensin receptor blocker (ARB) by using ambulatory blood pressure monitoring (ABPM) was never done. The aim of this randomized, double-blind, active-controlled, superiority trial was to compare BP lowering effect and variability indices of FMS with VAL at higher dose. Figure. No caption available. Design and method: Hypertensive patients who went through wash-out/run-in period for at least 2 weeks and had baseline systolic BP (SBP) over 140mmHg were randomized to FMS or VAL groups. Subjects were initially given standard starting dose of FMS, VAL (60 mg, 80 mg, respectively), then forced-titrated to double dose (120 mg, 160 mg, respectively) at week 2 and followed up to week 6. Sitting systolic and diastolic BP (SiSBP and SiDBP) were measured at baseline, 2 weeks and 6 weeks and ABPM was done at baseline and 6 weeks. Results: : Total 312 subjects were enrolled from 8 teaching hospitals in Korea (FMS, n = 155, 57.95 ± 8.07 years old, VAL, n = 157, 58.99 ± 7.06 years old). After 6 weeks of treatment, FMS demonstrated significantly higher BP reduction compared to VAL (SiSBP; 136.63 ± 15.56 vs. 140.12 ± 14.53 mmHg, SiDBP; 85.87 ± 10.51 vs. 87.71 ± 8.94 mmHg, p value 0.0298 and 0.0211, respectively). Table 1 demonstrated blood pressure measurement by ABPM and Table 2 demonstrated variability indices. Changes of night-time SBP was higher than day-time SBP in FMS group (−14.39 ± 1.33 vs. −16.73 ± 1.39 mmHg, p = 0.2253), but not significant. Conclusions: : FMS showed strong BP lowering effect than VAL all day long. FMS treated group showed greater blood pressure lowering effect on both day and night-time SBP. FMS also showed more BP changes at night which suggests possibility of restoring dipping pattern in non-dipping hypertensive patients.